1999
DOI: 10.1002/1529-0131(199901)42:1<69::aid-anr9>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autoantibodies to ribosomal P proteins in juvenile-onset systemic lupus erythematosus compared with the adult disease

Abstract: Objective. To determine the prevalence of anti-ribosomal P (anti-P) proteins in several groups of patients with juvenile-onset systemic lupus erythemato-sus (SLE) in comparison with the prevalence in adult SLE. Methods. Serum samples were pooled together from 3 cohorts of patients with juvenile-onset SLE in 3 different medical centers and from a miscellaneous group of juvenile-onset SLE patients whose samples were sent by regional physicians. Sera were studied for the presence of anti-P using 2 assays: Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 28 publications
6
60
1
1
Order By: Relevance
“…Recurrent fetal loss due to thrombosis of the placenta is one of the most prominent symptoms ofAPS (8). Anti-ribosomal P antibodies (anti-P), one of the anti-cytoplasmic antibodies, have also been found in patients, with a prevalence of 5 to 42% (9)(10)(11)(12)(13)(14). Anti-P is believed to be associated with neuropsychiatric disorders (12,15,16), as well as liver and kidney lesions in patients with SLE (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent fetal loss due to thrombosis of the placenta is one of the most prominent symptoms ofAPS (8). Anti-ribosomal P antibodies (anti-P), one of the anti-cytoplasmic antibodies, have also been found in patients, with a prevalence of 5 to 42% (9)(10)(11)(12)(13)(14). Anti-P is believed to be associated with neuropsychiatric disorders (12,15,16), as well as liver and kidney lesions in patients with SLE (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was suggested that anti-Rib-P antibodies are more prevalent in juvenile-onset SLE than in adult-onset SLE (27). An association of anti-Rib-P with neuropsychiatric manifestations of SLE (NPSLE) has been more controversial (1,4,5,11,12,15,19,25,29,31).…”
mentioning
confidence: 99%
“…[72][73][74][75][76] The few pediatric NPSLE studies so far have only demonstrated a higher prevalence of these and anti-dsDNA and anti-Sm antibodies, in childhood than adult onset SLE without any clear causal or pathogenic association yet elucidated. 4,77,78 Our group at University College London (UCL), recently described the observation that serum anti-Sm antibodies levels correlate positively with higher levels of nitrated nucleosomes, a serum marker of nitrosative stress, as measured by a novel capture ELISA. From our small number of patients with SLE from the UCL Hospital Lupus Cohort, we also made an observation that nitrated nucleosome levels significantly correlated with SLE disease activity and also significantly correlated with NPSLE involvement as per validated BILAG and ACR classification evaluation.…”
Section: Autoantibodiesmentioning
confidence: 99%